Effect of varying thickness of electroplated NiFe film on magnetic properties - Sulaiman, Nadzril; Yunas, Jumril; Yeop Majlis, Burhanuddin (2012)
The thickness variations of NiFe based magnetic core and its effects on magnetic properties have been investigated. The thin film core material is fabricated by using electroplating that may have direct effect on the performance on magnetic device. In this work, the main interest is on varying thickness of NiFe film that is being used as magnetic core material for a micro-scaled magnetometer. The magnetic properties of interest are coercivity and saturation magnetization. From the experiments, the relationship between the thickness of electroplated NiFe film and coercivity and saturation magnetization are determined. The low coercivity and low saturation magnetization can be achieved by increasing the core thickness. This relationship can be used to improve the functional of a micro magnetometer.